Hybrid organic–inorganic triguanidine arsenate dihydrate for ultraviolet nonlinear optical application. Issue 2 (20th December 2021) - Wang, Dongmei; Wei, Zhuangzhuang; Bai, Zhiyong; Liu, Lehui; Lin, Zhoubin; Zhang, Lizhen
Abstract : Introduction of the planar organic cation [C(NH2 )3 ] + into tetrahedronal inorganic arsenate generates a new ultraviolet nonlinear optical crystal. Abstract : Introduction of the planar organic cation [C(NH2 )3 ] + into tetrahedronal inorganic arsenate generates a new ultraviolet nonlinear optical crystal triguanidine arsenate dihydrate, [C(NH2 )3 ]3 AsO4 ·2H2 O, which exhibits a short ultraviolet absorption edge (210 nm), suitable second-harmonic generation response (0.9 × KDP), and moderate birefringene (0.0387 at 546 nm). Notably, by optimizing the growth conditions, transparent and wafer well-developed bulk single crystals can be easily prepared.